Human Resource Development In Knowledge-Based Economy: Role Of Higher Educational Institutions In Malaysia - Rasool, Ghulam (2007)
The ultimate goal of this study is to find out the required competencies in knowledge-based economies and the extent to which these competencies and skills are provided by the higher educational institutions in Malaysia.